ASPECTS OF INDEPENDENT STUDY AND EMERGENCY RETRAINING OF STUDENTS AND LEARNERS IN PHYSICS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines aspects of independent preparation, revision, and urgent retraining of students and learners in the physics course, particularly in semiconductor physics.It identifies the necessary educational materials, textbooks, electronic resources, and other supplementary teaching aids that enable students to independently and successfully master and review the physics course, especially semiconductor physics, thereby contributing to effective and competent work in the fields of ecology and environmental management.
Keywords: ecology, physical measuring instruments, atmosphere, radiation, radioactivity, independent study, emergency retraining, reference books, glossary, summary notes, electronic textbook, animated materials, physics textbooks, educational posters, semiconductor physics, physics problems, virtual laboratory work, electronic tests